2019
DOI: 10.3126/jpahs.v6i1.27073
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of fibular strut graft and two cannulated hip screws in neglected fracture neck of femur in adults - 10 years review

Abstract: Introductions: Avascular necrosis and non-union are common but when the neck of femur fracture in adult is neglected, the chances of complications rises. Among various treatment options, we report the outcome of free fibular strut graft along with two cannulated hip screws in neglected fracture neck of femur. Methods: The outcome analysis of ‘fibular strut graft and two cannulated hip screws’ was conducted in patients with fracture neck of femur who presented at least three weeks after the time of injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…4 Half of the studies summarized in this review are treating neglected femoral neck fractures. 8,10,12 These fractures remain a burden in developing countries. Neglected femoral neck fracture presents with shortening, severe external rotation of the lower extremity, upward displacement of the trochanter, with or without soft tissue contracture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Half of the studies summarized in this review are treating neglected femoral neck fractures. 8,10,12 These fractures remain a burden in developing countries. Neglected femoral neck fracture presents with shortening, severe external rotation of the lower extremity, upward displacement of the trochanter, with or without soft tissue contracture.…”
Section: Discussionmentioning
confidence: 99%
“…Seven patients had minor complains such as mild ache, ankle swelling after rigorous walking, and some weakness of long toe flexors and extensors Zahid et al 9 6 0 Other complications include screw migration in the joint space (1), graft migration into the joint space (3), and screw pullout (5). Chhetri et al 10 1 3 Complications were reported three weeks after intervention, including shortening (5), hip screws backing out (3), head cut through by screw (1), varus alignment (1), late infection (1), superficial infections (3), and donor site discomfort (4). Elgeidi et al 11 1 0 Pain was the most common morbidity in patients (7), which settled down in 2 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation